Bibliometric Analysis of Smart Public Governance Research: Smart City and Smart Government in Comparative Perspective - Petra Vujković; Dejan Ravšelj; Lan Umek; Aleksander Aristovnik (Social Sciences, 2022)
The concept of smart public governance (SPG) is gaining attention among researchers, policymakers, and practitioners around the world, especially in response to the modernisation of public administration through emerging technologies in both local (smart city) and national (smart government) levels. Spurred by the noticeable lack of understanding of the SPG concept, the paper aims to comprehensively examine the SPG research by considering the characteristic differences between the smart city and smart government concepts. Bibliometric analysis is based on the Scopus database, containing 775 documents published in the last two decades and facilitated by several established and innovative bibliometric approaches. The results reveal the growth of SPG research over time. Despite the smart city concept being the dominant focus in the SPG research, the smart government concept has been becoming more relevant in recent years, as indicated by some prominent documents published in reputable journals like Government Information Quarterly. Moreover, Anglo-Saxon countries are chiefly engaged in SPG research. However, New Zealand and South Korea are identified as countries with a stronger focus on the smart government concept. The results show the smart city concept is connected with several smart-related initiatives (e.g., smart transportation, smart living, smart energy, etc.), while the smart government concept is primarily associated with smart (de)regulation and smart grid. The findings may add to the understanding of the future development of SPG research, on both local and national levels.